2015
DOI: 10.1002/biof.1254
|View full text |Cite
|
Sign up to set email alerts
|

Human carotid atherosclerotic plaque protein(s) change HDL protein(s) composition and impair HDL anti‐oxidant activity

Abstract: High density lipoprotein (HDL) anti-atherogenic functions are closely associated with cardiovascular disease risk factor, and are dictated by its composition, which is often affected by environmental factors. The present study investigates the effects of the human carotid plaque constituents on HDL composition and biological functions. To this end, human carotid plaques were homogenized and incubated with HDL. Results showed that after incubation, most of the apolipoprotein A1 (Apo A1) protein was released fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Studies have also shown that PON1, an antioxidant marker, and SAA, an inflammation marker, move in opposite directions and indicate dysfunctional and a more proatherogenic form of HDL [15,23]. Inflammation and oxidative stress coexist in patients with chronic disease [15,24] and under these conditions native HDL may be converted into dysfunctional HDL [7,25] with altered proteins. These changes may contribute to the less protective and more atherogenic nature of HDL [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that PON1, an antioxidant marker, and SAA, an inflammation marker, move in opposite directions and indicate dysfunctional and a more proatherogenic form of HDL [15,23]. Inflammation and oxidative stress coexist in patients with chronic disease [15,24] and under these conditions native HDL may be converted into dysfunctional HDL [7,25] with altered proteins. These changes may contribute to the less protective and more atherogenic nature of HDL [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its reverse cholesterol transport and cholesterol efflux activity, HDL has various endothelial promoting and cardio-protective properties; it is antithrombotic, anti-inflammatory and an antioxidant [7,8,9]. PON1, an enzyme found mostly in bound form to HDL [10], in association with ApoA-1 [11], affords antioxidant capacity to HDL and may explain, in part, its anti-atherogenic function [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the lack of significant differences in the ApoA content of blood from animals fed normal diets (control) versus the content of this molecule in WGLL-treated rabbits maintained on high cholesterol (HCT) indicated a normalizing effect of the lyophilisate on this outcome. The significance of this result is that ApoA-I deficiency causes both hypertriglyceridemia and increased atherosclerosis in animal models [44], which can be counteracted by a WGLL-supported diet.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another finding observed in this study was an inverse relationship between HDL concentration and the lag time, which indicates that HDL reduces resistance to oxidizability process. 16,20 The most epidemiological studies indicate that plasma HDL is considered as a protective factor against coronary heart disease. The prevalence of atherosclerosis has been reported to be lower in the patients with high HDL levels.…”
Section: Discussionmentioning
confidence: 99%